Role of Non-Neuronal Cells in Body Weight and Appetite Control - Argente-Arizón, Pilar; Freire-Regatillo, Alejandra; Argente, Jesús; Chowen, Julie A. (Frontiers in Endocrinology, 2015)
The brain is composed of neurons and non-neuronal cells, with the latter encompassing glial, ependymal and endothelial cells, as well as pericytes and progenitor cells. Studies aimed at understanding how the brain operates have traditionally focused on neurons, but the importance of non-neuronal cells has become increasingly evident. Once relegated to supporting roles, it is now indubitable that these diverse cell types are fundamental for brain development and function, including that of metabolic circuits and they may play a significant role in obesity onset and complications. They participate in processes of neurogenesis, synaptogenesis and synaptic plasticity of metabolic circuits both during development and in adulthood. Some glial cells, such as tanycytes and astrocytes, transport circulating nutrients and metabolic factors that are fundamental for neuronal viability and activity into and within the hypothalamus. All of these cell types express receptors for a variety of metabolic factors and hormones, suggesting that they participate in metabolic function. They are the first line of defense against any assault to neurons. Indeed, microglia and astrocytes participate in the hypothalamic inflammatory response to high fat diet (HFD)-induced obesity, with this process contributing to inflammatory related insulin and leptin resistance. Moreover, HFD-induced obesity and hyperleptinemia modify hypothalamic astroglial morphology, which is associated with changes in the synaptic inputs to neuronal metabolic circuits. Astrocytic contact with the microvasculature is increased by HFD intake and this could modify nutrient/hormonal uptake into the brain. In addition, progenitor cells in the hypothalamus are now known to have the capacity to renew metabolic circuits and this can be affected by HFD intake and obesity. Here we discuss our current understanding of how non-neuronal cells participate in physiological and physiopathological metabolic control.